Konflik Agraria Antara Masyarakat Dengan Perusahaan Pemegang HPHTI di Kabupaten Pelalawan - Sobri S.IP., MA (SISI LAIN REALITA, 2017)
Agrarian conflict between the people living in the villages of the pelalawan district is due to the change of government policy related to the pattern of management of natural resources such as forest, land and river, from "subsistence" pattern to the pattern of industrialization in the forestry sector becoming the root of agrarian conflict in Riau province . The change of development policy from the pattern of Subsistence to the pattern of industrialization in the forestry and plantation sectors created by the government led to changes in the control of natural resources such as land, rivers and forests from the "Subsistence" pattern based on ulayat concept, to become widespread land tenure (monopoly) by the owners of capital (the corporations).